Sensitivity of Entomopathogenic Fungi and Bacteria to Plants Secondary Metabolites, for an Alternative Control of Rhipicephalus (Boophilus) microplus in Cattle - Nardoni, Simona; Ebani, Valentina V.; D’Ascenzi, Carlo; Pistelli, Luisa; Mancianti, Francesca (Frontiers in Pharmacology, 2018)
Boophilus (Rhipicephalus) microplus is a one host hard tick widespread in warm climates worldwide, responsible for great economic losses. To avoid resistance in ticks population, induced by the repeated administration of conventional acaricides and/or the presence of residues in the environment in meat and in milk, an alternative approach can be achieved using entomopathogenic microrganisms such as fungi and bacteria, or essential oils (EOs). The aim of the present study was to evaluate the in vitro sensitivity of Beauveria bassiana, Metarhizium anisopliae, Scopulariopsis sp, Bacillus thuringiensis and Proteus mirabilis to Eucalyptus globulus, Lavandula hybrida, Pelargonium graveolens EOs and to their main constituents such as lynalool, linalyl-acetate, geraniol, citronellol and 1,8 cineole. EOs has been chemically characterized by GC-MS. Fungal isolates were tested by a microdilution assay to achieve minimal inhibitory concentration (MIC) of both EOs and main components. The sensitivity of bacteria was evaluated by an agar disk diffusion. The results obtained show the feasibility of an integrate approach for an eco-friendly control of R. microplus by use of both entomopathogenic fungi and P. graveolens EO. L. hybrida could be an interesting alternative when B. bassiana is not employed. Conversely, a combined use of B. thuringiensis and EOs would not be advisable in the integrate control of ticks.